1 Clement a reader's edition - Klemens I. Papst ca. 1. Jh.; Bergren, Theodore A. 1952- (Washington, D. C. Catholic University of America Press, 2020)
Intro -- Table of Contents -- Introduction -- Acknowledgments -- 1 Clement -- Dictionary of Words Occurring Frequently In Early Christian Greek Literature -- Scriptural Quotations and Allusions in 1 Clement -- Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Klemens; Electronic books